OPTIMALISASI CITRA MRI WRIST JOINT DENGAN PENERAPAN 3D ISOTROPIK PADA PEMBOBOTAN PROTON DENSITY DI INSTALASI RADIOLOGI RSUP DR. M. DJAMIL PADANG - I Putu Eka Juliantara; Wellya Herlina; Triningsih Triningsih (Syntax Corporation Indonesia, 2022)
MRI is a medical imaging modality that works by utilizing hydrogen atoms in the body. Imaging that does not use ionizing radiation but uses an external magnetic field. MRI is able to provide good soft tissue contrast based on the nature of the tissue. The wrist joint is a complex joint consisting of several bones and joints. The bones of the wrist joint consist of the wrist including the distal radius and ulna, 8 carpal bones, and the proximal part consists of 5 metacarpal bones. This type of research is a quantitative study with an experimental approach. This research will be conducted by comparing isotropic 3D sequences and PDW TSE SPAIR Cor sequences. Data collection was carried out from May to July 2022 at the Radiology Installation of RSUP DR. M. Djamil Padang. The author took the Wrist Joint MRI examination data as many as 10 volunteer samples. Based on the results of the research conducted, the researchers concluded that the results of the Wilcoxon test for each anatomy were used to see differences in the clarity of anatomical information produced by the Isotropic 3D PDW sequence and the PDW TSE SPAIR Coronal sequence. So based on the results of the Wilcoxon test, the anatomical information on the Wrist Joint MRI examination is the most optimal in producing isotropic 3D sequence anatomical information higher than the PDW TSE SPAIR Coronal sequence which is produced from the anatomical criteria of Ligament, Cartilage, TFCC, Bone, except for cartilage anatomy criteria with the isotropic 3D PDW sequence has a lower value than the TSE SPAIR Coronal PDW sequence